Evaluation of elastic modulus and hardness of polylactic acid-based biocomposite by nano-indentation - Lutpi, Husniyah Aliyah; Anuar, Hazleen; Surip, Siti Norasmah; Bonnia, Noor Najmi (Trans Tech Publications, Switzerland, 2012)
This study focuses on the micromechanical properties of polylactic acid (PLA) reinforced with kenaf fiber (KF) and organo-montmorillonite (OMMT) hybrid biocomposite by using nanoindenter. Nanoindenter is an analytical device that can record small load and depth with high accuracy and precision which can be used to determine the modulus, hardness and other mechanical properties of nanomaterials. The result shows that the optimum properties of the hardness and elastic modulus were dominated by PLA-KF-OMMT hybrid composite.